(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2016)
In this work, we have investigated the exchange interaction of two electrons in double lateral quantum dot (which is the base of quantum gate) under effect of external magnetic field, electric field and inter dot distance between double dots. From similarity between double quantum dots and molecule, we have used molecular physics approaches (Hitler London and Hund Mullikan approximation method) to investigate our system. We also show the magnetization behavior as function of magnetic field.